Web-Based Interactive Multimedia Courseware for the ‘Discovering Computer’ in the Self-Learning Strategies Concept - Salman, Noralia Akilah; Mohamad Rasli, Roznim (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
Teknologi multimedia interaktif telah menyumbang kepada proses pengajaran dan pembelajaran yang lebih efektif khususnya dalam penggunaan perisian instruksional koswer. Tujuan kajian ini adalah untuk membangunkan koswer multimedia interaktif bagi pelajar universiti untuk mempelajari dengan lebih mendalam berkenaan komputer yang bertajuk Discovering Computer. Koswer ini dibangunkan dengan menggunakan metodologi ADDIE yang terdiri daripada modul pelajar, video pembelajaran dan koleksi latihan. Pengujian kebolehgunaan meliputi isi kandungan kursus, kebolehcapaian, reka bentuk antara muka dan kebolehfungsian dijalankan dengan menggunakan kaedah tinjauan kuantitatif yang melibatkan seramai 33 orang sampel. Sasaran utama koswer ini ialah pelajar universiti yang berumur di antara 18 tahun ke 25 tahun sahaja. Dapatan menunjukkan bahawa kandungan pembelajaran di dalam koswer ini adalah lebih menarik dan interatif berbanding pembelajaran menggunakan teknik pengajaran tradisional iaitu berasaskan buku. Selain itu, pengguna koswer ini dapat meningkatkan mutu dan prestasi pengajaran dan pembelajaran (bahan bantu mengajar) dan juga meningkatkan pengalaman dan motivasi pelajar. Web-Based Interactive Multimedia Courseware for the ‘Discovering Computer’ in the Self-Learning Strategies Concept Abstract: Interactive multimedia technology has contributed to a more effective teaching and learning process, especially in the use of instructional software. The purpose of this study is to develop an interactive multimedia courseware for university students to learn more about computer entitle Discovering Computer. This courseware is developed by using the ADDIE methodology comprises of student modules, learning videos and a collection of exercises. Software Usability testing consist of course content, accessibility, interface design and functionality were evaluated using a quantitative survey method that involving 33 samples respondents by student in different categories. The main target of this study is university student‘s aged between 18 and 25 years old. Findings indicate that the learning content in this book is more interesting and interactive than learning using traditional teaching technique, book based learning. In addition, this courseware can enhance the quality and performance of teaching and learning (teaching aids) and also improve student’s experience and motivation. Keywords: Computer Teaching and Learning, Interactive Multimedia Courseware, Self-Paced Learning Strategies, Teaching Aids.